2D Chiroptical Nanostructures for High‐Performance Photooxidants. (7th March 2018) - Xu, Liguang; Sun, Maozhong; Cheng, Ping; Gao, Rui; Wang, Hui; Ma, Wei; Shi, Xinghua; Xu, Chuanlai; Kuang, Hua
Abstract: Modulation of the chirality of solid‐like nanoscale membranous structures used as selective photooxidants is an important goal of chemical and materials science. Here, the fabrication of a chiral plasmonic nanoparticle monolayer film which is a highly selective photooxidant under circularly polarized light (CPL) in the visible‐light region is reported. The chiroptical activity of the film can be controlled by altering the amount and stereochemistry of amino acids. The experiments disclose that this stable and reusable catalyst is active in the selective oxidation of glucose enantiomers and CPL of opposite polarization gives around 10.3‐fold increase in conversion rates. The results reveal that the handedness of polarized light dominates the catalytic activity of the chiral film. It is demonstrated that the specific chiral binding of the amino acid ligands and the local field enhancement in the light‐limited regime regulates the selective photocatalytic performance, as confirmed by first‐principles density functional theory and physical field simulations. With the catalyst's signature ability for chiral recognition and switching of handedness of polarized light, the discovery provides a foundation for designing and tailoring chiral inorganic photooxidants. This research also sets an example for the development of light–matter interactions and polarized optics. Abstract : A chiral plasmonic nanoparticle monolayer film is developed to be a highly selective photooxidant under circularly polarized light (CPL) in the visible‐light region. The chiroptical activity can be controlled. The robust and reusable 2D nanostructures are active in the selective oxidation of chemical enantiomers and CPL of opposite polarization gives around 10.3‐fold increase in conversion rates.